Nano on reflection A number of experts from different areas of nanotechnology describe how the field has evolved in the last ten years - Bursten, JR; Roco, MC; Yang, W; Zhao, Y; Chen, C; Savolainen, K; Gerber, C; Kataoka, K; Krishnan, Y; Bayley, JHP; Nazar, L; Milana, S; et al. (Nature Publishing Group, 2016)
A decade ago, ‘nano’ was a word of tomorrow, signifying the promise of a future enhanced and streamlined by the torrent of possibilities that would come from single-atom control over the material world. Apple had just blazed a now well-worn path of cashing in on this cultural sentiment, releasing its firstgeneration iPod Nano in September 2005. Nanotechnology was hailed as a panacea to the economic and ecological malaise of the early 2000s, with the promise of cost-effective and relatively easy-to-produce solutions to problems as diverse as the energy crisis, chemotherapy and cybersecurity.